'Just because a doctor says something, doesn't mean that [it] will happen': self‐perception as having a Fertility Problem among Infertility Patients. Issue 3 (27th December 2017) - Leyser‐Whalen, Ophra; Greil, Arthur L.; McQuillan, Julia; Johnson, Katherine M.; Shrefffler, Karina M.
Abstract: Only some individuals who have the medically defined condition 'infertility' adopt a self‐definition as having a fertility problem, which has implications for social and behavioural responses, yet there is no clear consensus on why some people and not others adopt a medical label. We use interview data from 28 women and men who sought medical infertility treatment to understand variations in self‐identification. Results highlight the importance of identity disruption for understanding the dialectical relationship between medical contact and self‐identification, as well as how diagnosis acts both as a category and a process. Simultaneously integrating new medical knowledge from testing and treatment with previous fertility self‐perceptions created difficulty for settling on an infertility self‐perception. Four response categories emerged for adopting a self‐perception of having a fertility problem: (i) the non‐adopters – never adopting the self‐perception pre‐ or post‐medical contact; (ii) uncertain – not being fully committed to the self‐perception pre‐ or post‐medical contact; (iii) assuming the label – not having prior fertility concerns but adopting the self‐perception post‐medical contact; and (iv) solidifying a tentative identity – not being fully committed to a self‐perception pre‐medical contact, but fully committed post‐medical contact. (A virtual abstract of this paper can be viewed at:https://www.youtube.com/channel/UC_979cmCmR9rLrKuD7z0ycA ).